Spatial Patterns of Habitat Use of Wintering Tidal Marsh Birds Along the Mississippi Gulf Coast - Carlos Ramirez-Reyes; Kristine O. Evans; Mark S. Woodrey; Rachel Anderson; Jared Feura; Landon R. Jones; Raymond B. Iglay (Wetlands, 2026)

Improving Environmental and Social Targeting through Adaptive Management in Mexico's Payments for Hydrological Services Program - KATHARINE R. E. SIMS; JENNIFER M. ALIX‐GARCIA; ELIZABETH SHAPIRO‐GARZA; LEAH R. FINE; VOLKER C. RADELOFF; GLEN ARONSON; SELENE CASTILLO; CARLOS RAMIREZ‐REYES; PATRICIA YAÑEZ‐PAGANS (Conservation Biology, 2014)
Natural resource managers are often expected to achieve both environmental protection and economic development even when there are fundamental trade‐offs between these goals. Adaptive management provides a theoretical structure for program administrators to balance social priorities in the presence of trade‐offs and to improve conservation targeting. We used the case of Mexico's federal Payments for Hydrological Services program (PSAH) to illustrate the importance of adaptive management for improving program targeting. We documented adaptive elements of PSAH and corresponding changes in program eligibility and selection criteria. To evaluate whether these changes resulted in enrollment of lands of high environmental and social priority, we compared the environmental and social characteristics of the areas enrolled in the program with the characteristics of all forested areas in Mexico, all areas eligible for the program, and all areas submitted for application to the program. The program successfully enrolled areas of both high ecological and social priority, and over time, adaptive changes in the program's criteria for eligibility and selection led to increased enrollment of land scoring high on both dimensions. Three factors facilitated adaptive management in Mexico and are likely to be generally important for conservation managers: a supportive political environment, including financial backing and encouragement to experiment from the federal government; availability of relatively good social and environmental data; and active participation in the review process by stakeholders and outside evaluators. Mejorando los Objetivos Ambiental y Social Mediante el Manejo Adaptativo en el Programa de Pagos por Servicios Hidrológicos en México